THE ROOT OF THE TONGUE: NATURE THE PRIME ENOUNCER IN MANOJ KUROOR’S NILAM POOTHU MALARNNA NAAL - Siby, Nayantara (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Throughout human history, linguectomy is rampant everywhere. Hegemonic powers repress the tongues of the subjugated communities through multiple processes of silencing/ standardization. Nature and human language hold an intrinsic mutual tie. Manoj Kuroor’s novel Nilam Poothu Malarnna Naal is a brilliant attempt at recapturing the lost rapport with nature through reclaiming the cadences of the spoken language of the people. He narrates the story of the Panar community and their struggles in maintaining their native tongue and culture. The novel simultaneously resists linguacides and ecocides.